Influencia de las propiedades superficiales en reacciones de halogenación de sílice de origen biogénico - Segura Gómez, Enrique; Álvarez Guzmán, Gilberto; Gutiérrez Fuentes, José Alfredo; Martínez Rosales, J. Merced; Cervantes Jáuregui, Jorge Armando (Acta Universitaria, 2011)
Silica from biogenic origin is contained in rice hulls and is an important source of silicon materials. An important fact is the higher reactivity respect to mineral silica (quartz) and in consequence a lower energy is required for processing in certain applications. In this study, results from the reaction of chlorine gas and silica from rice hulls is reported with focus in the effect of textural properties in the reactivity of silica with chlorine. Taking into account the need of carbon as reduction agent in this reaction, it comes from the thermal reduction of the organic components of rice hull. To the resultant SiO2/C samples obtained at different temperatures and periods of time, textural properties were calculated. It was found that the highest surface area (260 m2/g) was obtained at 600 °C and 1 h of treatment. These samples were selected to perform the halogenations reactions at 750 °C. According to Si NMR in solution, silicon tetrachloride was the only silicon product.
Keywords: Array; Array; Array